2012
DOI: 10.1007/s00402-012-1493-8
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the diagnostic test accuracy of MRA and MRI for the detection of glenoid labral injury

Abstract: Level 2a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 75 publications
3
47
0
2
Order By: Relevance
“…Although conventional magnetic resonance imaging has been reported to identify labral pathology with sensitivities of 76% to 93% and specificities of 68% to 87%, magnetic resonance arthrography has been reported to have improved diagnostic results, with sensitivities ranging from 88% to 92% and specificities ranging from 92% to 93%. [24][25][26][27][28][29] When glenohumeral osseous deficiency is suspected, computed tomography (CT) scans are particularly helpful in determining the extent of glenoid and humeral bone loss in cases of instability. Compared with radiography, conventional CT, and magnetic resonance imaging, 3-dimensional CT has been shown to be the most reliable imaging modality for the quantification of glenoid and humeral bone loss and can be combined with arthrography to allow for simultaneous assessment of soft-tissue structures in addition to the osseous anatomy.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Although conventional magnetic resonance imaging has been reported to identify labral pathology with sensitivities of 76% to 93% and specificities of 68% to 87%, magnetic resonance arthrography has been reported to have improved diagnostic results, with sensitivities ranging from 88% to 92% and specificities ranging from 92% to 93%. [24][25][26][27][28][29] When glenohumeral osseous deficiency is suspected, computed tomography (CT) scans are particularly helpful in determining the extent of glenoid and humeral bone loss in cases of instability. Compared with radiography, conventional CT, and magnetic resonance imaging, 3-dimensional CT has been shown to be the most reliable imaging modality for the quantification of glenoid and humeral bone loss and can be combined with arthrography to allow for simultaneous assessment of soft-tissue structures in addition to the osseous anatomy.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Patients between the ages of 40 years and 60 years have an increased risk of clinically relevant rotator cuff tears (approximately 40%) and, consequently should undergo routine ultrasound/magnetic resinance imaging to assess cuff integrity. MRA is the investigation of choice (CTA is an accepted alternative if MRA is unavailable) to identify Bankart lesions with a sensitivity and specificity of 88% and 91% to 93% respectively 18,19 Sensitivity and specificity significantly increases when MRA is also performed with the shoulder in an abducted and externally rotated position (ABER) 20 CT is the most accurate at calculating glenoid bone loss 21 , a potential complication of recurrent instability. However, magnetic resinance imaging is also satisfactory and has the advantage of defining soft tissue abnormalities better Non-operative management .…”
Section: Further Investigationsmentioning
confidence: 99%
“…In their meta-analysis, Smith found that the specificities of MRI for superior labral tear and for Bankart lesions were only 74 and 56 percent respectively. For MRA, these values increased to 75 and 80 percent [30]. As already discussed, the differentiation between types I, III, and IV SLAP tears can also be problematic, with important consequences for the planning of surgery [28].…”
Section: Diagnosismentioning
confidence: 90%
“…Supplementation of this method with an intraarticular contrast agent (MRA) is frequently employed to provide greater accuracy, as assessed using arthroscopic diagnosis as a gold standard. In a recent meta-analysis of 60 studies, Smith found that the sensitivity and specificity of MRI for overall glenoid labral lesions were 76 percent and 87 percent, respectively, while for MRA the corresponding values were 88 percent and 93 percent [30]. The authors concluded that MRA provides a marginal improvement in diagnostic accuracy, at a cost of increased expense, invasiveness, and exposure to radiation.…”
Section: Diagnosismentioning
confidence: 99%